A formative evaluation of the Silence The Violence programme : a school-based violence prevention programme - Phillips, Lynn (2010)
Includes summary.Includes bibliographical references (leaves 63-68).This report presents the findings of a formative evaluation of the Silence The Violence (STV) programme, a school-based violence prevention initiative. The programme is implemented by an organisation known as Khulisa Services, which has service points in all nine provinces of South Africa. The main objective of the STV programme is to reduce verbal, emotional and physical violence in schools